BANGGA MENJADI PUSTAKAWAN - Armen Armen (UIN Imam Bonjol Padang, 2020)
Abstract: As a librarian, the author feels very proud to be a librarian. This pride is certainly not without reason. In the author's view, being a librarian is in fact a very exemplary profession and a very noble and honorable profession. Same is the case with other professions. Being a librarian, means we must be ready to serve many people. Serving the information needs of visitors, serving with a smile, and of course serving with sincerity and humility. The energy of a sincere heart ignites positive activities that benefit ourselves and others.Keywords: Proud to be a librarianAbstrak: Sebagai seorang pustakawan, Penulis merasa sangat bangga menjadi pustakawan. Kebanggaan ini tentunya bukan tanpa alasan. Dalam pandangan Penulis, menjadi pustakawan justru merupakan sebuah profesi yang sangat Membagagakan dan profesi yang sangat Mulia dan Terhormat. Sama halnya dengan profesi lainnya. Menjadi seorang pustakawan, berarti kita harus siap melayani banyak orang. Melayani kebutuhan informasi para pemustaka, melayani dengan senyuman, dan tentunya melayani dengan keikhlasan serta kerendahan hati. Energi hati yang ikhlas menyulut aktivitas positif yang bermanfaat untuk diri kita sendiri dan orang lain.Kata Kunci: Bangga Menjadi pustakawan